Clausewitz : a very short introduction - Howard, Michael, 1922-2019 (Very short introductions, 2002)
Karl von Clausewitz's study "On War" remains relevant today. Michael Howard explains Clausewitz's ideas in terms both of his experiences as a professional soldier in the Napoleonic Wars, and of the intellectual background of his time.